Expanding Super Edge-Magic Graphsâ - E. T. Baskoro; Y. M. Cholily (Institute for Research and Community Services (LPPM) ITB, 2004)
For a graph G, with the vertex set V(G) and the edge set E(G) an edge-magic total labeling is a bijection f from V(G)UE(G) to the set of integers 1,2,...., |V(G)|+|E(G) with the property that f(u) + f(v) +f(uv) = k for each uv elemen E(G) and for a fixed integer k. An edge-magic total labeling f is called super edge-magic total labeling if f(E(G)) = |V(G)+1, |V(G)+2,....., |V(G)+E(G)|. In this paper we construct the expanded super edge-magic total graphs from cycles C, generalized Petersen graphs and generalized prisms.